Physical layer security in DF full-duplex relaying network: performance analysis - Phu Tran Tin; Tan N. Nguyen; Van-Duc Phan; Minh Tran (Institute of Advanced Engineering and Science, 2021)
In this letter, the system performance of the DF full-duplex (FD) Relaying communication network is investigated with Physical Layer Security (PLS). In this system model, the source (S) and the destination (D) communicate via a helping relay (R) in the presence of the Eavesdropper (E). From the system model, we derive the closed-form expressions for Intercept Probability (IP) and secrecy outage probability (SOP). For verifying the correctness of the analytical analysis, the Monte Carlo simulation is conducted. In addition, the influence of the main system parameter on the system performance is investigated. Finally, the results show that the analytical and the simulation values agree well with each other.